Exceptional design in an iconic landscape? Interpretations of landscape and residential architecture in Dartmoor National Park - Tatum, Kirsten (Leiden University Library, 2018)
In England’s national parks, architecture represents an important and contested part of landscape planning inseparable from park conservation ideologies and policies. This paper investigates the competing landscape interpretations surrounding the design and planning of an unrealised new dwelling in Dartmoor National Park. In a landscape revered for its ‘iconic’ status, and on a site constrained by local planning policy, planning permission hinged on satisfying the conditions of a clause in national policy whereby a recognised ‘exceptional’ new dwelling might be permitted to override local planning restrictions. This research considers how different constructions of landscape identity influenced the conception and regulation of Dartmoor’s landscape as a context for new architecture. Discourse analysis of interviews and planning documents examines the range of landscape interpretations and notions of ‘appropriate’ architecture among key stakeholders, including locals, planners, and architects. Findings reveal significant rifts in aesthetic design discourses, which are influenced by conceptions of site, landscape character, the built cultural and historic context, and landscape enhancement. In summary, this paper considers the significance of conflicting landscape interpretations for the accommodation of new architecture in protected landscapes.